(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Many materials are used for root canal obturation but all of them possess certain drawbacks. In the present study compared the obturation quality of Glass ionomer cement containing chitosan root canal filling material with other regularly used materials by using dye penetration. Material and Methods: Thirty-six human roots were chosen for this study. After de-coronation of the teeth and separation of the desired roots, they were instrumented by the Protaper Universal system from S1-F4 and then divided into three major groups: Group 1, filled with experimental material (glass ionomer cement/ Chitosan); group 2, filled with gutta-percha with zinc oxide eugenol sealer; group 3, filled with gutta-percha with AH26. The evaluation was performed by radiographs post-obturation and by dye leakage test. Results: There was no significant difference between root canal obturation materials. Conclusions: The use of glass ionomer cement with chitosan root canal filling material improves the obturation quality of root canals.